2013
DOI: 10.3168/jds.2012-5636
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Associations between teat dimensions and milking-induced changes in teat dimensions and quarter milk somatic cell counts in dairy cows

Abstract: Although many studies have examined the relation between a wide range of factors and quarter milk somatic cell count (qSCC), including physical characteristics of the teat and changes in teat tissue due to milking, the effect of short-term, milking-induced changes in teat dimensions on somatic cell count has not yet been investigated. To identify teat dimensions and milking-induced changes in teat dimensions associated with qSCC, we conducted a longitudinal study (n(herds)=6, n(cows)=72, n(measurements)=12). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 22 publications
2
31
3
Order By: Relevance
“…Dairy cattle spend 12 to 14 h per day lying down (Tucker and Weary, 2004), and during this time their teats are intimately exposed to potential pathogens in their environment (Hogan et al, 1989). The risk of IMI has been previously associated with teat dimensions (Slettbakk et al, 1995;Zwertvaegher et al, 2013). In a recent case-control study, we demonstrated that increased diameter of the teat apexes of front teats was associated with increased risk of clinical mastitis (Guarín and Ruegg, 2016).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Dairy cattle spend 12 to 14 h per day lying down (Tucker and Weary, 2004), and during this time their teats are intimately exposed to potential pathogens in their environment (Hogan et al, 1989). The risk of IMI has been previously associated with teat dimensions (Slettbakk et al, 1995;Zwertvaegher et al, 2013). In a recent case-control study, we demonstrated that increased diameter of the teat apexes of front teats was associated with increased risk of clinical mastitis (Guarín and Ruegg, 2016).…”
Section: Introductionmentioning
confidence: 80%
“…Bacterial numbers on teat skin are indicative of increased potential exposure, but other mechanisms may be necessary for exposure to result in IMI. Among these, larger teat orifices and wider teat canals (Seykora and McDaniel, 1985), wider teat apexes of front teats (Guarín and Ruegg, 2016), or milking machine-induced changes on teats (Zwertvaegher et al, 2013) have been associated with increased risk of IMI.…”
Section: Resultsmentioning
confidence: 99%
“…Machine milking-induced short-term changes of teat tissue condition are defined as tissue responses to a single milking (Mein et al, 2001) and can be discriminated into congestion (intravascular accumulation of fluids) and edema (extravascular accumulation of fluids; Hamann and Mein, 1990). Short-term changes have been investigated in multiple studies using different techniques, including visual assessment (Hillerton et al, 2000), a modified spring-loaded caliper (Hamann and Mein, 1988), a 2-dimensional vision-based measuring device (Zwertvaegher et al, 2013), infrared thermography (Paulrud et al, 2005), and ultrasonography (Neijenhuis et al, 2001a). These short-term changes have been related to teat canal openness, penetrability, and susceptibility to new IMI (Zecconi et al, 1992;Neijenhuis et al, 2001a;Paulrud et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The canals of congested teats have been shown to close more slowly after milking (Neijenhuis et al, 2001), and this delayed closure of the teat canal is thought to result in a longer window of opportunity for mastitis, causing bacteria to pass through the teat canal (Mein et al, 1987;Zecconi et al, 1992;Gleeson et al, 2004). Thicker teats postmilking compared with premilking are associated with higher quarter SCC (Zwertvaegher et al, 2013).…”
Section: Introductionmentioning
confidence: 99%